Assessing The Influence of Work-Life Balance, Work Stress, And Workload on Employee Performance: Evidence From Champlung Mas Hotel Resort & Spa Legian Kuta Bali - I Wayan Satya Dwiantara; Ni Made Dwi Puspitawati; Tiara Carina (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Employee performance is the work achieved by an individual or group of individuals in a company in accordance with their respective authority and responsibilities, organizational objectives, without violating the law and without conflicting with morals and ethics. This study aims to determine the effect of work-life balance, work stress, and workload on employee performance at the Champlung Mas Resort & Spa Legian Kuta Bali Hotel. This study uses data analysis methods, namely multiple linear regression analysis and hypothetical testing, namely T-test analysis. The results show that work-life balance has a positive and significant effect on employee performance at Champlung Mas Resort & Spa Legian Kuta Bali. Work stress has a negative effect on employee performance at Champlung Mas Resort & Spa Legian Kuta Bali. Workload has a negative effect on employee performance at Champlung Mas Resort & Spa Legian Kuta Bali.